Development of pediatric orally disintegrating mini-tablets containing atomoxetine hydrochloride-?-cyclodextrin inclusion complex using experimental design - Ozyilmaz, Emine Dilek; Comoglu, Tansel (Taylor & Francis Ltd, 2022)
ObjectiveThe aim of the study was to develop and evaluate characteristics of orally disintegrating mini-tablet (ODMT) formulations including atomoxetine hydrochloride (ATO)/beta-cyclodextrin (beta-CD) inclusion complex for pediatric therapy of attention deficit and hyperactivity disorder (ADHD).MethodsDesign of experiment approach was used to develop ODMTs. The ODMTs were compressed using direct compression method with two different superdisintegrants (Parteck ODT(R) and Ac-Di-Sol(R)) and characterized with quality control tests. In vitro dissolution and taste studies were performed.ResultsThe hardness and friability values of the optimized three ODMT formulations were determined as 41.7 N, 42.4 N, and 40.8 N and 0.32%, 0.29%, and 0.42%, respectively. The disintegration time of all the optimized formulations was found to be less than one minute. In addition, dissolution profiles of ATO from optimized ODMTs were determined in four different dissolution media (distilled water, pH 1.2, 6.8, and 7.4) and it was determined that the maximum dissolved ATO amount reached at the end of 20 min.ConclusionAs a conclusion, the novel formulation of ODMTs with ATO/beta-CD inclusion complex was successfully developed for pediatric use.
Keywords: beta-CD inclusion complex; pediatric therapy of ADHD; orally disintegrating mini-tablets; factorial design; in vitro evaluation